METHODOLOGICAL APPROACHES TO BUILDING RESEARCH COMPETENCE OF FUTURE DOCTORS OF PHILOSOPHY DURING THEIR POSTGRADUATE STUDIES - Oliinyk Iryna (Alfred Nobel University Publisher, 2022)
The professional activity of a specialist in modern society is primarily determined by their ability to make competent information interactions. Definitely, information is one of the main resources for the scientific, technical and socio-economic development of society. It plays an important role in the process of educational space modernization where the formation of the ability to find, analyse and process this information takes on special importance, requiring the development of innovative approaches to the research competence shaping future Ph.Ds. in their postgraduate studies. The article is aimed at substantiation of methodological approaches to solving the problem of building research competence of future Doctors of Philosophy during postgraduate studies. The objectives of the paper are to define the meaning of the basic component of the article - "approach", to analyse the fundamental approaches that provide building research competence of future Doctors of Philosophy as well as to substantiate the expediency of their use. Complex methods for solving the problems of a scientific paper have been used, including theoretical analysis and synthesis of ideas, results, theoretical statements (explained in scientific literature), generalization and systematization of the results of available investigations of the highlighted issue. Study results. The modern educational system focuses on building future specialists' competence as a result of their readiness and ability to solve educational problems and carry out research activities. The present paper is devoted to the problem of training future Doctors of Philosophy during postgraduate studies because the transmission to new educational standards significantly increased the relevance of the problem of building research competence that determines a lecturer's ability to investigate, plan and organize his /her work effectively to achieve the predicted result. The analysis of scientific and pedagogical studies established the conceptual core of methodological approaches to building future specialist's competence during postgraduate studies. In order to have the holistic view of research competence, its structure and meaning, as well as the laws of its development in relation to future Doctors of Philosophy, fundamental methodological approaches have been systematized, namely acmeological, systemic, cluster, personality-oriented, technological, axiological, competence-based, praxiological, facilitative, participatory, synergistic, meta-subject, and hermeneutic ones. Taking into account the development of new standards and the features of educational paradigms that provide the effectiveness of building research competence of future Doctors of Philosophy, the above mentioned complex approaches have been considered as basic and optimal ones. The analysis of best practices clearly shows that there is no common vision of the principles of combining methodological approaches in solving the issue of building research competence. The article presents the experience of combining methodological approaches in solving the issue of building research competence based on the principle of mean full dominants. The author has found out that the use of these approaches will provide the successful process of building research competence of future Doctors of Philosophy, their ability to create fundamental scientific developments focused on the shaping of educational space that will develop and improve the personality qualities of future Doctors of Philosophy for successful self-realization.